Connection of I-beam to box-column by a short stub beam. (December 2016) - Erfani, Saeed; Asnafi, Ahmad Ali; Goudarzi, Alireza
Abstract: Box-columns are frequently used in moment resisting frames due to the numerous advantages they offer. Accordingly, bolted extended end-plate moment connections are widely used in steel structures due to their advantages such as easy fabrication and fast erection. However, some problems such as inaccessibility to the inside of box-columns for assembling the continuity plates as well as fastening the bolts prevent the wide applications of these connections to connect I-beams to box-columns. The present study aims to solve these problems by proposing two new connection configurations. In these connection models, a short stub beam is used to connect I-beams to box-columns by bolted end plate connection. These connection models have different force transfer mechanisms so that the use of continuity plates should be necessary for the first model while it can be omitted in the second model. The behavior of these connection models is investigated under cyclic loading by using finite element method. To validate modeling techniques used in this study including the mesh and element types, material properties and contact elements, the numerical results of an end-plate connection model are compared with experimental data. Then, for each connection model, eight specimens including four-bolt unstiffened and eight-bolt stiffened extended end-plate connections are analyzed under cyclic loading. All the specimens studied in this program were shown to undergo the 0.05 rad total story drift with the AISC seismic provision requirements being satisfied. Highlights: Two new connection configurations are proposed to connect I-beams to box-columns. The two configurations are different in force transfer mechanism. The behavior of these connection models is investigated under cyclic loading using finite element method. The modeling method was verified against experimental results The analysis results approved that the proposed connections are satisfying AISC seismic provisions.